Immunoaffinity purification and characterization of mitochondrial membrane-bound D-3-hydroxybutyrate dehydrogenase from Jaculus orientalis - Mountassif, Driss; Andreoletti, Pierre; El Kebbaj, Zakaria; Moutaouakkil, Adnane; Cherkaoui-Malki, Mustapha; Latruffe, Norbert; El Kebbaj, M'hammed Saïd (BMC biochemistry, 2008)
Background The interconversion of two important energy metabolites, 3-hydroxybutyrate and acetoacetate (the major ketone bodies), is catalyzed by D-3-hydroxybutyrate dehydrogenase (BDH 1 : EC 1.1.1.30), a NAD + -dependent enzyme. The eukaryotic enzyme is bound to the mitochondrial inner membrane and harbors a unique lecithin-dependent activity. Here, we report an advanced purification method of the mammalian BDH applied to the liver enzyme from jerboa ( Jaculus orientalis ), a hibernating rodent adapted to extreme diet and environmental conditions. Results Purifying BDH from jerboa liver overcomes its low specific activity in mitochondria for further biochemical characterization of the enzyme. This new procedure is based on the use of polyclonal antibodies raised against BDH from bacterial Pseudomonas aeruginosa . This study improves the procedure for purification of both soluble microbial and mammalian membrane-bound BDH. Even though the Jaculus orientalis genome has not yet been sequenced, for the first time a D-3-hydroxybutyrate dehydrogenase cDNA from jerboa was cloned and sequenced. Conclusion This study applies immunoaffinity chromatography to purify BDH, the membrane-bound and lipid-dependent enzyme, as a 31 kDa single polypeptide chain. In addition, bacterial BDH isolation was achieved in a two-step purification procedure, improving the knowledge of an enzyme involved in the lipid metabolism of a unique hibernating mammal. Sequence alignment revealed conserved putative amino acids for possible NAD + interaction.